DESIGN AND IMPLEMENTATION OF AUTOMATIC LIGHT CONTROL WITH BIDIRECTIONAL COUNTING SENSOR - Muhammad, Nura Idris; Yahaya Abdullahi, Muhammad; Nasiru, Murtala (FUDMA JOURNAL OF SCIENCES, 2023)
This paper present design and Implementation Automatic Light Control with Bidirectional counting Sensor. In the design, Light Control with Bidirectional Counting Sensor is proposed to be used so that controller-based model is adopt to count the number of persons entering or leaving a particular building and accordingly turn on or turn off lighting in the building. A sensor is used with counters to count the number of people entering or leaving a particular building. The logic behind the design is that whenever a person enters, it counts up and when a person leaves its count down. The light control of the system is actualized when an individual enter and remains off when left. The designed is achieved using infrared light sensor and combination of array counter.  When implemented, the design can be used in public places like malls or library to restrict the flow of people.
Keywords: Astable; Common cathode; Electrical energy; Flip-flop; Infrared